Synthesis, Physicochemical Properties, and Ion Recognition Ability of Azulene-Based Bis-(Thio)Semicarbazone - Anamaria Hanganu; Catalin Maxim; Andreea Dogaru; Adrian E. Ion; Coralia Bleotu; Augustin M. Madalan; Daniela Bala; Simona Nica (Molecules)
Azulene-1,3-bis(semicarbazone), 1, and azulene-1,3-bis(thiosemicarbazone), 2, were synthesized by the acid-catalyzed condensation reactions of semicarbazide and thiosemicarbazide, respectively, with azulene-1,3-dicarboxaldehyde in stoichiometric amounts. Compounds 1 and 2 were identified by high-resolution mass spectrometry and characterized by IR, 1H-NMR, 13C-NMR, and UV-vis spectroscopic techniques. Crystal structure determination of azulene-1,3-bis(thiosemicarbazone) shows that the thiosemicarbazone units exhibit a syn-closed conformation, with both arms oriented in the same direction and adopting an E configuration with respect to the imine linkages. Both hydrazones are redox active and showed fluorescence emission at 450 nm upon excitation at 350 nm. The bis-semicarbazone showed no affinity for anions nor for mercury(II) metal cation. Instead, the bis-thiosemicarbazone showed a lower affinity for chloride anions, but enhanced affinity for binding/poisoning Hg2+ ions. Both compounds were tested against osteosarcoma MG63 cell lines, exhibiting low antiproliferative activity with comparable IC50 values of 473.08 μM and 472.40 μM for compounds 1 and 2, respectively. Despite this limited antiproliferative effect, further analysis using propidium iodide staining revealed a concentration-dependent decrease in cell viability, with high concentrations inducing a marked reduction in cell number, accompanied by morphological changes characteristic of apoptosis and necrosis.